Insurance Companies Investment Portfolio Management in Ukraine: Current State and Priorities - Liudmyla CHVERTKO; Nataliia GVOZDEJ; Oksana VINNYTSKA; Tetiana KORNIIENKO; Svitlana PODZIHUN; Yuliia MELNYCHUK (Communications of International Proceedings, 2021)
The features of the formation of the investment portfolio of insurance companies are generalized and the necessity of its management is substantiated. It is noted that the structure of the investment portfolio of the insurance company directly depends on the specifics of the insurance business, and the management of its formation is reduced to ensuring the required level of profitability at a lower level of expected risk. The peculiarities of the formation of the investment portfolio of insurance companies are generalized and the necessity of its management is substantiated. It is noted that the structure of the investment portfolio of the insurance company directly depends on the specifics of the insurance business, and the management of its formation is reduced to ensuring the required level of profitability at a lower level of expected risk. The main sources of formation of investment resources of insurers in Ukraine are described, the analysis of dynamics of their components is carried out. The structure of assets of insurance companies has been assessed and investment priorities for allocating insurance reserves have been determined. It was found that the investment portfolio of insurance companies in the country is imperfect: in recent years, the assets of companies have increased due to bank deposits; their share of stock instruments, in particular, corporate securities, is low; Insurers practically did not invest in some types of assets. Given the importance of investment activities of insurers for the economy and the current situation in this area, the need to optimize the structure of the investment portfolio of insurance companies and expand the investment of insurance reserves, the main condition of which is to improve management efficiency.
Keywords: Insurance Market; Insurance Company; Insurance; Investment Activity; Investment Portfolio; Investment Policy; Insurance Reserves; Asset Structure.